Digital Natives and online learning in police students - Mićović, Dragoslava; Beko, Lidija (NBP. Nauka, bezbednosti, policija, 2022)
Although not a novelty in education, online teaching and learning has come to the fore with the Covid-19 pandemic. Before 2019, it was an option for certain categories of learners and the new technologies enabled its expansion. The expansion of online learning prompted a number of relevant researches accordingly. The new reality created by the pandemic has forced many educational institutions to move to cyberspace, changing both the teachers’ and learners’ perception of education. The aim of our qualitative research was to investigate the perception of the students of the University of Criminal Investigation and Police Studies in Belgrade, Serbia, regarding the English Language 2 course, but also regarding their online education in general. The paper will first present some facts about distance/online learning, then some previous research on online education and finally the results of the present research.